Spatio-temporal evolution and driving factors of landscape pattern in minority villages: a case study of Zahan Village in Hainan Province - Shan Zhang; Jiaming Xie; Weifang Liu; Yupeng Zhu (Journal of Environmental Engineering and Landscape Management, 2024)
Ethnic minority settlements, as an important medium for the transmission of ethnic cultures, are also a key resource for accelerating the development of ethnic minorities and the regions where they are located. Currently, research on landscape patterns focuses on traditional villages and ancient villages, whereas there is a relative lack of discussion on ethnic minority settlements. This study focuses on the multi-ethnic Zahan Village in Hainan Province, adopting the analysis methods of landscape pattern index and land-use transfer matrix, based on the theoretical framework of landscape ecology, to systematically analyze the spatial and temporal characteristics of the landscape pattern of the village and its patterns between 2007 and 2022, and to qualitatively analyze the influencing factors of its landscape changes from two dimensions, namely, humanities and nature. Research findings: (1) As the dominant landscape type, the proportion of woodland (although decreasing year by year) still exceeds 80%, whereas other land types, such as watersheds and grasslands, are gradually transformed into construction land and arable land, whose increment is significant. (2) During the study period, Throughout the study period, the landscape homogeneity of Zahan Village became better and better, the landscape types tended to be richer, and the spatial heterogeneity of the landscape also increased. (3) The area of woodland landscapes shows a decreasing trend from year to year, whereas construction land and arable land show an overall increasing trend, and the area of watersheds and meadows also decreases slightly. (4) The village landscape is mainly spatially “clustered,” concentrated in the center and southern part of the village, with a few “dots” distributed in the east and northwest, and the overall trend is spreading from the center to the periphery. (5) The evolution of village landscapes is influenced by a combination of human factors, including demographic, economic, and policy factors, as well as natural geographic factors, such as topography, climate change, and precipitation. The study provides theoretical support and practical guidance for the sustainable development of Zahan Village, as well as valuable experience and inspiration for the optimal development of other minority villages.